Comparison of the cutting force, power, tool life and torque in the end milling of modified AISI P20 tool steel - P. Vinothi, S Parawa Karan (2009)
The aim of this study is to make comparison of the cutting force, power, torque and tool life in the end milling of modified AISI P20 tool steel with aid of statistical method by using coated carbide cutting tool under various cutting conditions. The first and second order cutting force equations are developed using the response surface methodology (RSM) to study the effect of four input cutting parameters which is cutting speed, feed rate, radial depth and axial depth of cut on cutting force, power, torque and tool life. In general, the result that been obtained from the mathematical model are in good agreement with that obtained from the experiment data’s. It was found that the feed rate, cutting speed, axial depth and radial depth played a major role in determining the cutting tools. The predictive models in this study are believed to produce values of the longitudinal component of the cutting force close to those readings recorded experimentally with a 95% confident interval.